Novel transparent MgSiON thin films with high hardness and refractive index. (September 2016) - Ali, Sharafat; Paul, Biplab; Magnusson, Roger; Greczynski, Grzegorz; Broitman, Esteban; Jonson, Bo; Eklund, Per; Birch, Jens
Abstract: There is an increasing demand for glass materials with better mechanical and optical properties for display and electronic applications. This paper describes the deposition of novel thin films of MgSiON onto float glass substrates. Amorphous thin films in the MgSiON system with high nitrogen and magnesium contents were deposited by reactive RF magnetron co-sputtering from Mg and Si targets in Ar/N2 /O2 gas mixtures. The thin films studied span an unprecedented range of compositions up to 45 at% Mg and 80 at% N out of cations and anions respectively. Thin films in the MgSiON system were found to be homogeneous and transparent in the visible region. Mechanical properties like hardness (H) and reduced elastic modulus (Er ) show high values, up to 21 GPa and 166 GPa respectively. The refractive index (1.87–2.00) increases with increasing magnesium and nitrogen contents. Highlights: MgSiON thin films were deposited by reactive RF magnetron sputtering. The Mg and N contents in the thin films can be tuned by Mg target power. MgSiON films are transparent in the visible region. MgSiON films have high values of hardness up to 21 GPa and reduced elastic modulus values up to 166 GPa. Refractive index at 633 nm ranging from 1.87 to 2.